The emotional impact of surveillance programs for pancreatic cancer on high‐risk individuals: A prospective analysis. Issue 6 (10th March 2020) - Paiella, Salvatore; Marinelli, Veronica; Secchettin, Erica; Mazzi, Maria Angela; Ferretto, Francesca; Casolino, Raffaella; Bassi, Claudio; Salvia, Roberto
Abstract: Objective: Literature shows that emotional status can influence participation in screening/surveillance programs, and that screening/surveillance programs may alter the psychological well‐being of subjects examined. This study aims to assess if participating in a surveillance program for pancreatic cancer early detection is associated with abnormal levels of psychological distress in high‐risk individuals (HRIs), compared to the general population. Methods: Fifty‐four HRIs participating in a magnetic resonance cholangiopancreatography (MRCP)‐based surveillance program completed several psychological assessment questionnaires, investigating global functioning, self‐efficacy, perceived stress, coping abilities, and social support. The questionnaires were administered by a clinical psychologist after the MRCP but before the subjects were informed about the results of the scans. The HRIs were subjects with strong familiarity of pancreatic cancer and/or carriers of known genetic mutations related to cancer susceptibility. The psychological assessment was made at the time of the first examination. Results: The population was characterized by an overall good psychological status. Scoring of our sample was comparable to the general population norms. The HRIs showed decent global functioning, high self‐efficacy levels, low perceived stress in the last month prior to examination, efficient emotion‐focused coping strategies, and an adequate social support system. The younger subjects' subpopulation only revealed higher levels of stress. Conclusions: From a psychological point of view, an MRCP‐based pancreatic cancer annual surveillance seemed not to influence the HRIs' psychological well‐being, unless in young people. Further studies are needed to better establish if there are any changes in distress levels over time and how emotional status influences participation in surveillance programs.